Geometrical Optics Process Image-Based Worksheets for Enhancing Students’ Higher-Order Thinking Skills and Self-Regulated Learning (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study intended to prove whether process image-based worksheets of geometrical optics could enhance students’ higher-order thinking (HOTS) and self-regulated learning (SRL). This was quasi-experimental research of non-equivalent control group design. This research was conducted to grade 8 junior high school students at a junior high school in Jember district studying the geometrical optic. The sample was 70 students; 35 students belonged to an experimental group and the other 35 students in a control group. The HOTS data were obtained from test results and the SRL data were collected from questionnaire results. To determine the effect of using the worksheets on the students’ HOTS and SRL, carried out was an independent t-test at a significance level of (2-tailed) α = 0.05. The results showed that the worksheets had a significant effect on the HOTS seen from α 0.05 and that the tcountttable at df = 68. In addition, the worksheets also owned a significant effect on the students’ SRL seen from α0,05 and that the tcount = 14,692 (ttable). Thus, it concluded that the learning with the worksheets had a significant influence on the junior high school students’ HOTS and SRL which are required for preparing their life in the 21st century.